DAMPAK PEMBERIAN LABEL MISKIN KEPADA KELUARGA PENERIMA BANTUAN PKH DI JORONG TANJUNG DURIAN KEC. SANGIR JUJUAN KAB. SOLOK SELATAN - Hidayat, M. Rahmat; Rahmadani, Sri; Erningsih, Erningsih (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research examines about The Impact Of Labeling Poor On PKH Recipient Families In Jorong Tanjung Durian, Sangir Jujuan District South Solok Regency. This study aims to describe the impact of labeling poor in Jorong Tanjung Durian Nagari Padang Limau Sundai, South Solok Regency. The approach used in this study is a descriptive qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation studies. The unit of analysis in this study is PKH recipient family. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study can be concluded that the impact of labeling poor on families receiving PKH assistance in Jorong Tanjung Durian, Sangir Jujuan District, South Solok Regency is (1). PKH recipient families feel awkward in society. (2). PKH recipient families become a byword in society. (3). PKH recipient families are belittled in society. (4).   Have the opportunity for their children to receive scholarships at school. (5). Opportunity to receive assistance again in the future.